A Geometric Measure for the Violation of Utility Maximization - Jan Heufer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Revealed Preference offers nonparametric tests for whether consumption observations can be rationalized by a utility function. If a consumer is inconsistent with GARP, we might need a measure for the severity of inconsistency. One widely used measure is the Afriat efficiency index (AEI). We propose a new measure based on the extent to which the indifference surfaces intersect the budget hyperplanes. The measure is intuitively appealing and, as a cutoff-rule evaluated by Monte Carlo experiments, performs very well compared to the AEI. The results suggest that the new measure is better suited to capture small deviations from utility maximation.
Keywords: C14; C60; D11; D12; 330; Consumer choice; efficiency index; GARP; nonparametric tests; revealed preference; Offenbarte Präferenzen; Konsumtheorie; Nutzentheorie; Nichtparametrisches Verfahren; Statistischer Test; Theorie